THE DYNAMICS OF POLITICIANS' SILATURAHMI TO KIAI BEFORE ELECTIONS IN INDONESIA: AN ANALYTICAL STUDY BASED ON ELITE THEORY AND SIYASAH SYAR’IYYAH - Lisa Hertiana; Supriyadi; Arif Sugitanata; Muhammad Hasyied Abdurrasyied (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The seasonal phenomenon of politicians silaturahmi to Kiai (Islamic scholars) ahead of elections in Indonesia reflects a strategy by politicians to gain support by leveraging the influence of Kiai as respected spiritual leaders with extensive social networks. This study aims to reveal the dynamics, influence, and controversies surrounding this practice and analyze how political elites utilize their relationships with Kiai to secure votes. The research employs a literature review with a qualitative approach and descriptive-analytical nature, referencing the elite theory of Vilfredo Pareto and Gaetano Mosca, as well as the principles of Siyasah Syar’iyyah. The findings indicate that the practice of politicians silaturahmi to Kiai before elections in Indonesia, although rooted in solid cultural traditions and viewed as a form of respect, is often used to gain blessings and moral support from Kiai, which is then leveraged in political campaigns. However, this approach also attracts criticism for potentially blurring the lines between religion and politics and posing the risk of transactional support that can undermine the integrity of Kiai. The analysis based on Vilfredo Pareto and Gaetano Mosca’s elite theory reveals how political elites and Kiai mutually benefit from each other to maintain their power and legitimacy. Meanwhile, from the perspective of Siyasah Syar’iyyah, the study emphasizes the importance of justice, transparency, and balance in Kiai’s political involvement. It highlights the need for political education based on Islamic values to empower the community in a healthy democratic process. Thus, this research highlights the complexity of interactions between religion, culture, and politics in Indonesia, demonstrating how traditional values and the influence of religious figures like Kiai remain significant in shaping the political dynamics of the country. Abstrak Fenomena musiman silaturahmi politisi ke Kiai menjelang pemilu di Indonesia mencerminkan strategi politisi untuk meraih dukungan dengan memanfaatkan pengaruh Kiai sebagai pemimpin spiritual yang dihormati dan memiliki jaringan sosial luas. Berdasarkan hal tersebut, penelitian ini bertujuan untuk mengungkap dinamika, pengaruh, dan kontroversi yang melingkupi praktik tersebut, serta menganalisis bagaimana elite politik memanfaatkan hubungan dengan Kiai untuk meraih suara. Penelitian ini memanfaatkan studi kepustakaan dengan jenis penelitian kualitatif dan sifat penelitian deskriptif-analitis yang merujuk pada teori elite politik Vilfredo Pareto dan Gaetano Mosca serta Siyasah Syar’iyyah. Hasil penelitian menunjukkan bahwa, praktik silaturahmi politisi ke Kiai menjelang pemilu di Indonesia, sering digunakan untuk mendapatkan restu dan dukungan moral dari Kiai, yang kemudian dimanfaatkan dalam kampanye politik. Namun, pendekatan tersebut mengundang kritik karena dapat mengaburkan batas antara agama dan politik serta menimbulkan risiko dukungan transaksional yang merusak integritas Kiai. Analisis teori elite politik Vilfredo Pareto dan Gaetano Mosca mengungkapkan bagaimana elite politisi dan Kiai saling memanfaatkan untuk mempertahankan kekuasaan dan legitimasi mereka. Sementara itu, dalam perspektif Siyasah Syar’iyyah menekankan pentingnya keadilan, transparansi, dan keseimbangan dalam keterlibatan politik Kiai, serta menyoroti kebutuhan akan pendidikan politik yang berbasis nilai-nilai Islam untuk memberdayakan masyarakat dalam proses demokrasi yang sehat.